The Macro-Fiscal Aftermath of Weather-Related Disasters : Do Loss Dimensions Matter? - Gerling, Kerstin (IMF Working Papers; Working Paper ;, 2017)
Weather-related natural disasters and climate change pose interrelated macro-fiscal challenges. Using panel-VARX studies for a sample of 19 countries in Developing Asia during 1970 to 2015, this paper contributes new empirical evidence on the dynamic adjustment path of growth and key fiscal variables after severe weather-related disasters. It does not only show that output loss can be permanent, but even twice as large for cases of severe casualties or material damages than people affected. Meanwhile, key fiscal aggregates remain surprisingly stable. Event and case studies suggest that this can reflect both a deliberate policy choice or binding constraints. The latter can make governments respond through mitigating fiscal policy efforts such as ad hoc fiscal rebalancing and reprioritization. The findings help better customize disaster preparedness and mitigation efforts to countries' risk exposure along a particular loss dimension.